Charge and Discharge Properties of a Ni-Co-based Layered Double Hydroxide Positive Electrode for Aqueous Zinc Batteries - Hikaru SUGIHARA; Satoshi OGAWA (Electrochemistry)
Nickel hydroxide is well known as a positive active material in nickel-cadmium and nickel-metal hydride batteries; its redox potential is close to that of the oxygen evolution reaction (OER), and it is known that the OER occurs simultaneously with a charging reaction when a battery is nearly fully charged. For this reason, nickel hydroxide electrodes are incorporated into designs where the oxygen generated at a positive electrode is absorbed by a negative electrode. However, when zinc is used as the negative active material, a dense separator is required to suppress zinc dendrites, making it difficult to design such an oxygen absorption system. In this study, we focused on nickel-based layered double hydroxide (LDH), instead of nickel hydroxide, to develop a cathode with low oxygen generation. We found that a Ni-Co LDH can be used as a positive electrode and can be charged with almost no oxygen generation up to the fully charged state. The expression capacity depended on the Ni content in the host layer, and a maximum of approximately 280 mAh g−1 was obtained. The output performance of the LDH electrode was comparable to that of the nickel hydroxide electrode, but the input performance was found to be significantly greater. These results suggest that nickel-based LDH can be used as a cathode active material in aqueous zinc anode batteries instead of nickel hydroxide.